Tribological and residential air conditioning performance using SiO2-TiO2/PVE nanolubricant - Wan Azmi, Wan Hamzah; M. F., Ismail; N. N. M., Zawawi; Rizalman, Mamat; S., Safril (ELSEVIER, 2024)
Applying nanoparticles as an additive may increase the lubrication performance of the oil. The present paper evaluates the tribological performance of SiO2-TiO2 nanoparticles in PVE lubricant and its effect on the system's performance in residential air conditioning (RAC). The hybrid nanolubricants with a concentration from 0.003 to 0.01% at a 50:50 ratio were tested using the four-ball tribological method and then applied in a customised RAC test rig. The friction coefficient and wear scar diameter were evaluated to synthesise nanolubricant anti-wear effect on a paired surface. The coefficient of performance (COP), cooling capacity, power consumption, and energy efficiency ratio (EER) were analysed to understand the influence of SiO2-TiO2/PVE nanolubricant in the RAC system. About 25% reduction in frictional coefficient was discovered when the nanoparticles were added into lubricant with a concentration of 0.005%. Applying nanolubricant in the RAC system can reduce compressor work and power consumption, increase the refrigerant flow rate and cooling capacity, and increase the COP and EER. Maximum enhancement of 39.2% and 52.7% for COP and EER were found for nanolubricant at concentrations of 0.005%. The 0.005% concentration is the nanoparticle's concentration threshold for SiO2-TiO2/PVE, as the higher concentration may lead to the performance of a pure lubricant.